The response of chrysanthemum plant cv. 'Debonair' to pinching date and leaves spraying with tyrosine - Saeed, Abdul Karim Abdul Jabbar Muhammad; Mahmoud, Catherine Adnan (Journal of agricultural, environmental and veterinary sciences, 2017)
The experiment was conducted in the lath house of the research station of horticulture department and landscape gardening/college of agriculture/university of  diyala to study the response of chrysanthemum plant cv. 'Debonair' with flowers in violet color to pinching date, which included three levels (without pinching, pinching after 15 and 30 days of transplanting) and foliar spray with tyrosine at four levels (50, 100 and 150 mg/l, as well as foliar spray with distilled water as a control treatment). The research was carried out as a factorial experiment (3×4) in split plots according to a randomized complete blocks design (RCBD) with three replicates. Treatments of pinching date represented the main plots and treatments of foliar spray with tyrosine were the secondary plots. The results can be summarized as follows:Pinching date was significantly affected on vegetative and flowering growth characteristics of chrysanthemum plant. It was found that the highest rate of plant height was achieved in control treatment (without pinching) and significantly superior to the pinching treatments after 15 and 30 days of transplanting which did not differ significantly between them. Pinching treatment after 15 days of transplanting led to a significant increase in number of branches/plant, number of leaves/plant, leaves area/plant, relative chlorophyll content in the leaves, percentage of total carbohydrates in leaves, number of flowers/plant and petals content of total anthocyanins, while Late pinching treatment (30 days after transplanting) delayed date of appearance of first flower and a significant reduction in flower diameter. Foliar spray with tyrosine led to improving all vegetative and flowering characteristics of chrysanthemum plant. Foliar spray at concentration of 100 mg/l was significantly superior in giving the best results for plant height, number of leaves/plant, leaves area/plant, relative chlorophyll content in the leaves, percentage of total carbohydrates in leaves, number of flowers/plant, flower diameter, age of flower on plant, dry weight of flower and petals content of total anthocyanins, while treatment at concentration of 150 mg/l resulted in earliness on date of appearance of first flower.Interaction between pinching date and foliar spray with tyrosine had a significant effect on all vegetative and flowering growth characteristics. Treatment of P15×Tyr100 gave the best results for the number of branches/plant, number of leaves/plant, leaves area/plant, relative chlorophyll content in leaves, vegetative dry weight, percentage of total carbohydrates in leaves, number of flowers/plant, age of flower on plant and petals content of total anthocyanins, while treatment of P0×Tyr100 was significantly superior in earliness on date of appearance of first flower, increase flower diameter and flower dry weight.
Keywords: Dawoodi plant; earring top; foliar spray; tyrosine